Host DNA depletion can increase the sensitivity of Mycobacterium spp. detection through shotgun metagenomics in sputum - Kok, Nienke A.; Peker, Nilay; Schuele, Leonard; de Beer, Jessica L.; Rossen, John W. A.; Sinha, Bhanu; Couto, Natacha (Frontiers in Microbiology, 2022)
Identification and phenotypic drug-susceptibility testing for mycobacteria are time-consuming and challenging but essential for managing mycobacterial infections. Next-generation sequencing (NGS) technologies can increase diagnostic speed and quality, but standardization is still lacking for many aspects (e.g., unbiased extraction, host depletion, bioinformatic analysis). Targeted PCR approaches directly on sample material are limited by the number of targets that can be included. Unbiased shotgun metagenomics on direct material is hampered by the massive amount of host DNA, which should be removed to improve the microbial detection sensitivity. For this reason, we developed a method for NGS-based diagnosis of mycobacteria directly from patient material. As a model, we used the non-tuberculous mycobacterium (NTM) Mycobacterium abscessus. We first compared the efficiency of three different DNA extraction kits for isolating DNA (quality and concentration). The two most efficient kits were then used in a follow-up study using artificial sputum. Finally, one extraction kit was selected and further evaluated for DNA isolation from a patients’ sputum mixture spiked with M. abscessus at three concentrations (final concentrations 108, 107, 106 CFU/mL). The spiked sputum samples were processed with and without saponin treatment (ST) in combination with DNAse treatment prior to bacterial DNA extraction to evaluate the recovery of bacteria and depletion of host DNA by PCR and Illumina sequencing. While Ct values of the qPCR targeting mycobacterial ITS DNA remained rather stable, Ct values in the qPCR targeting the human β-actin gene increased by five Ct values in ST samples. In subsequent Illumina sequencing, a decrease of 89% of reads mapped to the human genome was observed in ST samples. The percentage of reads mapped to M. abscessus (108 CFU/mL) increased by 89%, and the sequencing depth increased two times when undergoing ST. In conclusion, the sensitivity of M. abscessus detection in artificial sputum was increased using a saponin pre-treatment step. The saponin followed by the DNase I treatment approach could be efficiently applied to detect and characterise mycobacterial infections, including tuberculosis, directly from sputum.